A retrospective clinical study of dolutegravir- versus efavirenz-based regimen in treatment-naïve patients with advanced HIV infection in Nanjing, China - Zhong, Mingli; Li, Mengqing; Qi, Mingxue; Su, Yifan; Yu, Nawei; Lv, Ru; Ye, Zi; Zhang, Xiang; Xu, Xinglian; Cheng, Cong; Chen, Chen; Wei, Hongxia (Frontiers in Immunology, 2023)
Currently, there are limited data related to the efficacy and safety of ART regimens, as well as factors influencing immune recovery in antiretroviral therapy (ART)-naïve patients with advanced HIV infection, especially in China. We designed a single-center, retrospective cohort study from March 1, 2019, to May 31, 2022, at The Second Hospital of Nanjing, China. ART-naïve adults with advanced HIV infection (CD4+ T-cell count < 200 cells/μL) who met the study criteria were included. The plasma viral load (VL), CD4+ T-cell count, CD4/CD8 ratio, treatment discontinuation, and immune reconstitution inflammatory syndrome (IRIS) events were collected to compare the efficacy and safety of the dolutegravir (DTG) and the efavirenz (EFV) regimens. Factors of immune recovery were analyzed using the Cox regression model. Study enrolled 285 ART-naïve adults with advanced HIV-1 infection, of which 95 (33.3%) started regimens including DTG and 190 (66.7%) were treated with EFV. After ART initiation, the proportion of patients with HIV-1 RNA < 50 copies/mL was higher (22.5% versus 6.5%, P < 0.001) in those on DTG-based regimens at month 1, but no significant difference at other follow-up points. Compared to the baseline, the median CD4+ T-cell count and CD4/CD8 ratio increased significantly during follow-up both in the EFV and the DTG groups. However, the CD4+ T-cell count increased greater in patients on DTG-based regimens at months 6, 12, 24, and 36 (P < 0.05). A total of 52 (18.2%) patients discontinued treatment, with no significant difference between ART regimens in treatment discontinuation rates. Only 7 patients reported IRIS, without significant difference between ART regimens (P=0.224). Overall, 34.0% (97/285) achieved a CD4+ T-cell count ≥ 350 cells/μL during follow-up. Age (P < 0.001), baseline CD4+ T-cell count (P < 0.001), baseline VL (P < 0.001) and ART regimens (P = 0.019) were associated with the CD4+ T-cell count ≥ 350 cells/μL after adjusting for potential confounders. Among ART-naïve adults with advanced HIV infection, it appeared that DTG-based regimens were better options for initial therapy compared to regimens including EFV; in addition, ART regimens, age, baseline VL and CD4+ T-cell count were associated with immune recovery.